Neuropilin-1 in Transplantation Tolerance - Campos-Mora, Mauricio; Morales, Rodrigo A.; Gajardo, Tania; Catalan, Diego; Pino-Lagos, Karina (Frontiers in Immunology, 2013)
In the immune system, Neuropilin-1 (Nrp1) is a molecule that plays an important role in establishing the immunological synapse between dendritic cells (DCs) and T cells. Recently, Nrp1 has been identified as a marker that seems to distinguish natural T regulatory (nTreg) cells, generated in the thymus, from inducible T regulatory (iTreg) cells raised in the periphery. Given the crucial role of both nTreg and iTreg cells in the generation and maintenance of immune tolerance, the ability to phenotypically identify each of these cell populations in vivo is needed to elucidate their biological properties. In turn, these properties have the potential to be developed for therapeutic use to promote immune tolerance. Here we describe the nature and functions of Nrp1, including its potential use as a therapeutic target in transplantation tolerance.